2018
DOI: 10.1136/bmjqs-2017-007684
|View full text |Cite
|
Sign up to set email alerts
|

Variable effectiveness of stepwise implementation of nudge-type interventions to improve provider compliance with intraoperative low tidal volume ventilation

Abstract: Audit and feedback tools in conjunction with default changes improve provider compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…Of the 11 community‐based studies, five (45%) were randomized controlled trials, 38,45‐48 one was cluster‐randomized, 43 one was quasi‐randomized (alternate weeks), 39 and the remaining four (36%) were pre‐post studies40‐42,44: two single‐site and two multi‐site with controls (one with randomized allocation to intervention, the other unclear). Of the 11 hospital‐based studies, seven were single site pre‐post comparisons, 49‐52,54,56,59 one was a two site pre‐post comparison without a control, 53 one was a multi‐site pre‐post with one site non‐randomly allocated to intervention, 57 one was a multi‐site with multiple interventions rolled out at different times (non‐uniformly) across sites, 58 and one was a qualitative study 55 . We summarize the study types in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 11 community‐based studies, five (45%) were randomized controlled trials, 38,45‐48 one was cluster‐randomized, 43 one was quasi‐randomized (alternate weeks), 39 and the remaining four (36%) were pre‐post studies40‐42,44: two single‐site and two multi‐site with controls (one with randomized allocation to intervention, the other unclear). Of the 11 hospital‐based studies, seven were single site pre‐post comparisons, 49‐52,54,56,59 one was a two site pre‐post comparison without a control, 53 one was a multi‐site pre‐post with one site non‐randomly allocated to intervention, 57 one was a multi‐site with multiple interventions rolled out at different times (non‐uniformly) across sites, 58 and one was a qualitative study 55 . We summarize the study types in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Nudges that sought to utilize predispositions to social norms also reported varied results ranging from no statistically significant differences through to an absolute change of 20%. Two audit and feedback studies 52,58 reported changes ranging from non‐significant through 16%. Two commitment message studies 41,52 were associated with similar changes ranging from not statistically significant through to 20%.…”
Section: Resultsmentioning
confidence: 99%
“…Much more effective (and likely more sustainable) was changing the default ventilator setting to a lower set volume. 21 When done correctly, PDSA cycles will also give important insights into barriers to implementation and sustainability of the 'active ingredient(s)' mentioned above. One notable example comes from an intervention intended to improve timely delivery of antibiotics to febrile, immunocompromised children in the emergency department.…”
Section: Planning For Sustainment In Practicementioning
confidence: 99%
“…All national and international guidelines have reported how adequate LN yield could significantly improve survival in patients with oral cancer, however there is no recommended intervention for clinical practice. Interventions based on the theories of behavior economics are summarized by the acronym NUDGE and has been explored in the healthcare field [ 21 23 ]. Penn Medicine, for example, has used this strategy widely.…”
Section: Discussionmentioning
confidence: 99%